A simple method to debond a cement-retained implant-supported fixed partial denture from its abutment screw connection: a case report - Elboraey, A.N. (2021)
Screw loosening of a cement-retained, implant-supported fixed partial denture causes the abutment and restoration to be completely separated as one unit from the implant body. In such circumstances, drilling of an access hole through the restoration is made to retrieve the abutment screw connection, and a new restoration is then fabricated. The cement was dissolved and the fixed partial denture was easily separated from the abutment screw connections thus avoiding damage of the restoration.